Is working from home changing the meaning of work? - Sebastian Bähr; Bernad Batinic; Matthias Collischon (PLoS ONE, 2026)
Especially since the COVID-19 pandemic, working from home (WFH) has become a common practice in the workplace. This raises the question of whether WFH changes the non-monetary benefits of work, such as job quality or social contacts. Thus, in this article, we investigate how working from home affects Jahoda’s latent functions of employment as well as job quality measures. To this end, we use panel data from the German Panel Study Labour Market and Social Security (PASS) and estimate the effects of changing work patterns on the aforementioned outcomes. Our findings reveal basically no effects of WFH on job quality measures and latent benefits. This, in contrast to anecdotal evidence, implies that WFH does not harm psychological well-being.